From a phenomenological to a geomechanical approach to landslide hazard analysis. Issue 9 (20th October 2016) - Cotecchia, Federica; Santaloia, Francesca; Lollino, Piernicola; Vitone, Claudia; Pedone, Giuseppe; Bottiglieri, Osvaldo
Abstract : The diagnosis of landsliding at the slope scale resulted from synergic geohydromechanical analyses of the slope factors, which should represent the first step to assess landslide hazard. According to the methodological approach discussed in the paper, the landslide hazard analysis should start from a phenomenological interpretation of the slope behaviour, including the definition of the slope factors, getting then to a quantitative prediction of the slope evolution with time. This quantitative evaluation should result from limit equilibrium analyses and numerical modelling, both of them performed considering the outcomes of the phenomenological reconstruction. Therefore, the understanding of the slope factors and of the landslide mechanism at the slope scale should drive the landslide hazard assessment, through analyses performed for different levels of diagnosis (phenomenological, analytical and numerical). Some landslides, representative for chain slopes in the Italian peninsula, are discussed in the paper in order to show the maturity of the geohydromechanical diagnosis of landslide hazard and, hence, to properly design the mitigation actions. A methodology for intermediate to regional landslide hazard assessment, based on geomechanical interpretations, is finally proposed.